2011
DOI: 10.1177/0276146711421786
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Status Orientations on Purchase Preference for Foreign Products in Vietnam, and Implications for Policy and Society

Abstract: In this article, the authors examine the impact of status orientations on consumer purchase preferences for foreign products, an emerging disposition in Vietnam. Both qualitative (in-depth interviews and focus groups) and quantitative methods (survey with urban Vietnamese consumers) were employed in this investigation. The results of structural equation modeling (SEM) provided empirical evidence for the positive influence of modern status orientation (MSO) on willingness to buy imported products. Traditional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Brazil), customers have experience with modern retailing and can develop better store image perceptions than customers in less developed markets, where customers continue to shop mainly in traditional retail outlets. Diallo (2012) also highlights the importance of image factors for customer purchase behaviour in Brazil's retail environment, whereas Vietnamese customers emphasise other factors, such as perceived store value or traditional orientation status (Diallo, 2015;Mai and Smith, 2012). Therefore, we propose: H1.…”
Section: Hypothesis Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Brazil), customers have experience with modern retailing and can develop better store image perceptions than customers in less developed markets, where customers continue to shop mainly in traditional retail outlets. Diallo (2012) also highlights the importance of image factors for customer purchase behaviour in Brazil's retail environment, whereas Vietnamese customers emphasise other factors, such as perceived store value or traditional orientation status (Diallo, 2015;Mai and Smith, 2012). Therefore, we propose: H1.…”
Section: Hypothesis Developmentmentioning
confidence: 98%
“…The service dimension also demands careful management; personnel training should mirror the local culture. Mai and Smith (2012) stress the importance of status orientation for foreign product purchases by Vietnamese customers. Consequently, modern retailers should actively seek to offer high-value merchandise and develop their ability to express care for others in Vietnam, as well as in Brazil, where service is a key element for customers who consider social interaction paramount.…”
Section: Managerial Implicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the present findings support the contention that "consumer affinities could be an attractive option for overcoming ethnocentric barriers" (Oberecker et al, 2008, p. 51). It thus can be concluded that although multiple studies have recognized the adverse influence of CET on consumer transnational buying decisions (Ishii, 2009;Klein et al, 1998;Mai and Smith, 2012;Suh and Kwon, 2002), this is not the case for products from the affinity country.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Nguyen et al (2008) have found that consumer positively influenced imported product judgement such as the level of awareness, understanding and acceptance of the values of other culture. Moreover, Nguyen and Smith (2012) identified Vietnamese consumers have negative impact of ethnocentrism and the positive influence of modern status orientation such placing a high value on luxury objects, being rich, and being talented enough to earn a high income, thus they willingness to buy imported products and travel oversea countries.…”
Section: Business and Economic Researchmentioning
confidence: 99%